2017
DOI: 10.1016/j.jaad.2016.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term safety outcomes with ixekizumab from 7 clinical trials in psoriasis: Etanercept comparisons and integrated data

Abstract: Ixekizumab had an acceptable safety profile with no unexpected safety findings during ixekizumab maintenance in psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
112
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 38 publications
18
112
0
6
Order By: Relevance
“…This finding was expected and is in alignment with longer-term IXE studies in patients with plaque psoriasis 27 . The AIESP safety analysis, including safety data from all 52 weeks of this study, demonstrated safety and tolerability consistent with the known safety profile of IXE.…”
Section: Discussionsupporting
confidence: 86%
“…This finding was expected and is in alignment with longer-term IXE studies in patients with plaque psoriasis 27 . The AIESP safety analysis, including safety data from all 52 weeks of this study, demonstrated safety and tolerability consistent with the known safety profile of IXE.…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, these treatments suffer from long-term disadvantages including severe side effects (induction of cancer and infections because of completely blocking physiological functions of IL-17 or IL-23), and critically when the treatments stop, all disease symptoms will not only immediately rebound back, but the disease conditions will often get much worse as balance of your immune system becomes deleterious, it do occur clinically (personal communications). The observed development of ulcerative colitis and Crohn during ixekizumabe trial [11,12] is another good example of deleterious immune system by the biologic.…”
Section: Biologic Drugs Worsen Imbalanced Physiological Systemmentioning
confidence: 99%
“…Indeed, various infections have been observed clinically, which include, but are not limited to, infections of the upper respiratory tract and TB [11,12]. It has been also reported that Ixekizumab induces nonmelanoma skin cancers (NMSC), and inflammatory bowel diseases (both ulcerative colitis and Crohn's disease) -another good example of imbalanced immune system worsening.…”
Section: Biologic Drugs Worsen Imbalanced Physiological Systemmentioning
confidence: 99%
See 2 more Smart Citations